The transcription factors DcHB30 and DcWRKY75 antagonistically regulate ethylene-induced petal senescence in carnation (Dianthus caryophyllus) - Xu, Han (Journal of experimental botany, 2022)
© The Author(s) 2022. Published by Oxford University Press on behalf of the Society for Experimental Biology. All rights reserved. For permissions, please email: journals.permissionsoup.com.